Amniotic Fluid Embolism in Post Caesarean Section - Defrin Defrin; Heri Farnas (Universitas Andalas, 2020)
Background: According to WHO, around 73% of maternal deaths globally are caused by direct obstetric causes. The amniotic fluid embolism is a life-threatening obstetric emergency characterized by sudden cardiopulmonary system failure and can be accompanied by Disseminated Intravascular Coagulation (DIC). The amniotic fluid embolism event usually occurs during labor and birth, but can also occur immediately in the post partum period or after pregnancy termination. About 56% of women will not survive for first 2 hours after the acute event. Amniotic fluid embolism is an unpredictable event, so that no prophylactic intervention can be carried out effectively and the handling and enforcement of a diagnosis that still debatable.Objective: To report maternal deaths due to amniotic fluid embolism post cesarean sectionMethod: Case ReportCase: Reported case of a 30 years old woman with an initial diagnosis in emergency departement with decreased consciousness due to Severe hypoxia due to Pulmonary emboli due to Amniotic fluid emboli on P2A0L2 post Cesarean Section first day of puerperium. The patient experienced a sudden loss of consciousness accompanied by severe shortness of breath after 6 hours after cesarean section surgery in a private hospital. After initial examination and treatment by administering oxygen through the Nonrebreathing Mask, there was no improvement in the O2 saturation value and then the patient was intubated by the anesthetist. After intubation, the O2 saturation value still does not increase, then the patient suddenly experiences cardiac arrest and followed with cardiac resuscitation for 2 cycles accompanied by resuscitation drugs then the patient returns to spontaneous circulation. From the cardiology department, inotropic therapy was given and echocardiographic investigations were carried out. On echocardiographic examination, they found McConnel's sign which showed suspicios of pulmonary embolism. At the time the patient will be moved to the intensive care unit, the patient experiences a cardiac arrest for the second time, then resuscitation is performed again for 2 cycles, but it does not work and the patient is declared dead.Conclusion: Amniotic fluid embolism is an obstetric emergency condition that cannot be predicted and has a high mortality rate. Treatment is supportive to support the cardiopulmonary system and management of coagulopathy that may occur.Keywords: maternal mortality, amniotic fluid embolism